2013
DOI: 10.1111/ijd.12208
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma‐associated skin cancer: incidence, natural history, and clinical management

Abstract: The link between immunosuppression and skin cancer has been well described. The two most common situations involving immunosuppression-associated skin cancer are solid organ transplantation and non-Hodgkin lymphoma (NHL), including chronic lymphocytic leukemia (CLL). Patients with lymphoma are more likely to have development of a secondary malignancy, with skin cancer being the most common. The most common types of skin cancer in patients with NHL/CLL include melanoma, squamous cell carcinoma, basal cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 66 publications
0
39
1
2
Order By: Relevance
“…Given the increasing use of vemurafenib and dabrafenib in melanoma, and because malignant melanoma is overrepresented in the NHL population (~2.3-3.1 fold) (38,39), the progression or development of CLL in such patients must be anticipated. Although BRAFmutant melanoma and CLL can occur together, as seen in our patient, the typical patients with BRAF-mutant melanomas are …”
Section: Methodsmentioning
confidence: 99%
“…Given the increasing use of vemurafenib and dabrafenib in melanoma, and because malignant melanoma is overrepresented in the NHL population (~2.3-3.1 fold) (38,39), the progression or development of CLL in such patients must be anticipated. Although BRAFmutant melanoma and CLL can occur together, as seen in our patient, the typical patients with BRAF-mutant melanomas are …”
Section: Methodsmentioning
confidence: 99%
“…Non-Hodgkin lymphoma (including chronic lymphocytic leukemia) has been associated with KC risk in prior studies (7, 22, 23), and KC diagnosis is also associated with subsequent non-Hodgkin lymphoma risk (23, 24). This reciprocal pattern suggests a common underlying cause for both cancer types, such as a shared genetic predisposition or underlying immune dysfunction.…”
Section: Discussionmentioning
confidence: 95%
“…Most notably, solid organ transplant recipients have markedly increased risk of cutaneous SCC and BCC compared to the general population (35). Elevated risk of cutaneous SCC and BCC has also been identified in human immunodeficiency virus (HIV)-infected people and non-Hodgkin lymphoma patients (6, 7), and there is evidence of high skin cancer risk among bone marrow transplant recipients (8). …”
Section: Introductionmentioning
confidence: 99%
“…Chronic lymphocytic leukaemia (CLL) patients have a greatly increased risk of developing cutaneous squamous cell carcinoma (cSCC), which can be particularly aggressive, as reflected by increased levels of recurrence and metastasis. Consequently, cSCC is a major contributor to the mortality of CLL patients (Brewer et al , ; Velez et al , ). New Zealand (NZ) has one of the highest national rates of cSCC and we have previously reported that cSCC rates in CLL patients from a single NZ centre are three‐fold higher again.…”
Section: Patient and Tumour Characteristics Of Samples With Or Withoumentioning
confidence: 99%